Brain volumetric reductions in patients with thrombotic thrombocytopenic purpura - José Thiago de Souza de Castro; Simone Appenzeller; Letícia Rittner; Diedre Santos do Carmo; Fernanda A. Orsi; Fabiano Reis (PLoS ONE, 2025)
Introduction Thrombotic thrombocytopenic purpura (TTP) is a life-threatening disorder caused by a deficiency of a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13 (ADAMTS13). The recognition of increased morbidity and mortality in patients after recovery suggests that TTP may become a chronic disease with possible multiple adverse outcomes throughout life. Neurological disorders may occur in the acute phase of TTP due to several pathophysiological mechanisms. These mechanisms include the formation of microvascular thrombosis in capillaries or small arteries of the central nervous system (CNS), leading to transient or permanent ischemic brain damage. However, the causes underlying chronic neurological involvement in TTP are not fully understood, particularly in long-term survivors. Therefore, the aim of this study is to evaluate brain volumetry in TTP patients in remission and to correlate it with the neurological involvement associated with the disease. Methodology The study cohort includes 16 consecutive patients diagnosed with TTP between 1995 and 2016 at the Hospital de Clinicas, Universidade Estadual de Campinas (HC-UNICAMP), in Brazil. We performed MRI of the patients’ skull. Brain volume and parts of the central nervous system were analyzed and segmented using FreeSurfer. Results The CNS volumetry of 16 TTP survivors was analyzed and compared with that of 20 age- and sex-matched controls. TTP survivors showed a reduction in intracranial volume (1,019 cubic liters (L 3 )) compared to the control group (1,280 L 3 ), with a P value of 0.0003. The nucleus accumbens showed a significant reduction on the left side (469 mm 3 in TTP survivors X 605 mm 3 in controls, P = 0.02). The cerebellar cortex showed a reduction on the right side (44176.50 mm 3 in TTP survivors X 47283.15 mm 3 in control group, P = 0.05) and on the left side. Conclusion Our study demonstrated a significant reduction in brain and nucleus accumbens volume in patients with TTP compared with a healthy control group. These findings suggest a possible lasting impact of TTP on the CNS and highlight the importance of continued monitoring and intervention to reduce neurological complications in patients after the acute phase of the disease. Future studies are needed to validate our results and elucidate the mechanisms underlying the brain changes observed in patients with TTP. Our findings provide valuable information for developing more effective treatment strategies and improving the quality of life of patients with TTP.